COSMOLOGICAL MODERATION AND ECOLOGICAL ETHICS AMONG THE DAYAK HINDU BUDHA BUMI SEGANDU COMMUNITY IN INDRAMAYU - Zamzami Zamzami; Nuni Oktaviani; M. Agung Badawi (STAI ALHIKMAH Jakarta, 2026)
AbstractThis study examines how the Dayak Hindu Budha Bumi Segandu community in Losarang, Indramayu, West Java, constructs ethical life and religious moderation through its cosmology of nature. It responds to a gap in Indonesian religious moderation scholarship, which has largely focused on formal religions, state policy, interreligious dialogue, and anti-extremism programs, while local belief systems, lived religion, ecological ethics, and indigenous communities remain underexamined. Using a qualitative case-study design informed by phenomenological inquiry, the research draws on observation in the community environment, ritual spaces, and the padepokan; semi-structured interviews with 15 informants from five categories; and documentary materials collected during field engagement in 2025. Data were analyzed through transcription, initial coding, thematic clustering, triangulation across sources, member checking, and interpretive reading of participants' meanings. The findings show that the community understands alam, in emic terms, as the immediate source and sustaining ground of life. This worldview is articulated through Sejarah Alam Ngaji Rasa and embodied in kidung recitation, night bathing, sunbathing, family discipline, non-coercive interaction, and respect for social boundaries. The article argues that the community offers a carefully qualified model of cosmological moderation: a form of moderation grounded in human responsibility toward nature, self-restraint, respect for difference, non-violence, and accommodation of local culture. Rather than claiming direct reduction of radicalism, the study concludes that Dayak Indramayu local wisdom contributes to social harmony and non-violent coexistence within Indonesia's Muslim-majority plural society. ABSTRAKPenelitian ini mengkaji bagaimana komunitas Dayak Hindu Budha Bumi Segandu di Losarang, Indramayu, Jawa Barat, membangun etika hidup dan moderasi beragama melalui kosmologi mereka tentang alam. Kajian ini menjawab celah dalam studi moderasi beragama di Indonesia yang selama ini lebih banyak menyoroti agama formal, kebijakan negara, dialog antaragama, dan program anti-ekstremisme, sementara sistem kepercayaan lokal, agama yang dihayati, etika ekologis, dan komunitas kepercayaan lokal masih kurang dikaji. Dengan desain studi kasus kualitatif yang diinformasikan oleh pendekatan fenomenologis, penelitian ini menggunakan observasi di lingkungan komunitas, ruang ritual, dan padepokan; wawancara semi-terstruktur dengan 15 informan dari lima kategori; serta bahan dokumenter yang dikumpulkan selama keterlibatan lapangan pada 2025. Analisis data dilakukan melalui transkripsi, pengodean awal, pengelompokan tema, triangulasi sumber, member checking, dan pembacaan interpretif atas makna yang diberikan partisipan. Temuan menunjukkan bahwa komunitas memahami alam, dalam pengertian emik, sebagai sumber langsung sekaligus dasar penopang kehidupan. Pandangan ini diartikulasikan melalui Sejarah Alam Ngaji Rasa dan diwujudkan dalam pembacaan kidung, mandi malam, berjemur, disiplin keluarga, interaksi non-koersif, dan penghormatan terhadap batas sosial. Artikel ini berargumen bahwa komunitas tersebut menawarkan model moderasi kosmologis secara proporsional, yaitu bentuk moderasi yang bertumpu pada tanggung jawab manusia terhadap alam, pengendalian diri, penghormatan terhadap perbedaan, anti-kekerasan, dan akomodasi budaya lokal. Tanpa membuat klaim langsung tentang pengurangan radikalisme, penelitian ini menyimpulkan bahwa kearifan lokal Dayak Indramayu berkontribusi pada harmoni sosial dan koeksistensi non-kekerasan dalam masyarakat Indonesia yang mayoritas Muslim tetapi plural.